Urgensi Limitasi Masa Periode Anggota Legislatif di Indonesia - Abu Main, Ahmad Zulal; Habiburrohman, Muhammad (Sosio Yustisia: Jurnal Hukum dan Perubahan Sosial, 2023)
Indonesian lawmakers have not limited the periodicity of how many times a member may serve. It leads to a decline in the sensitivity of the members who have repeatedly acted to care more about the people. On the other hand, experienced legislature members are increasingly familiar with using budgets, further fueling the practices of abuses of power, corruption, collusion, and nepotism. This problem is interesting to examine, especially regarding the urgency limitation of legislative member terms in Indonesia. This study uses normative judicial research methods with conceptual, statute, and comparative approaches. The study results showed that the legislature deserved to have limited periods as a form of power limitation to prevent the practice of abuse of power and regeneration of political parties. It is confirmed by the data of abuse of power by several sitting legislatures and the course of limited periods imposed by other states.